Efeitos do exercício físico na destreza manual, sintomas motores e plasticidade cerebral em indivíduos com doença de Parkinson - Menacho, Maryela Oliveira (Universidade Federal de São Carlos, 2025)
Parkinson’s disease is the second most common progressive neurodegenerative disorder and is characterized by symptoms such as resting tremor, bradykinesia, rigidity, and postural instability, which significantly affect upper limb function in patients. Physical exercise is a non-pharmacological intervention alternative for these patients, as it can contribute significantly to improving quality of life. Therefore, this thesis was divided into two studies. The first aimed to gather the available literature on the effects of physical exercise on upper limb function in individuals with Parkinson’s disease through a systematic review. A systematic search was conducted using the PubMed, Embase, CENTRAL, PEDro, Scopus, and Web of Science databases, including the following terms: Parkinson’s disease, exercise/physical therapy, upper limb, and their respective entry terms. These terms were combined using Boolean operators (AND/OR) according to each database. A total of 15 randomized controlled trials were included, which performed the following interventions: task-oriented training, virtual reality/game therapy, training of activities of daily living, robotic therapy, training with a musical instrument, eccentric strengthening, constraint-induced movement therapy, manual dexterity training, and exercises with therapeutic mass. In conclusion, activity-based training is a viable option to improve manual dexterity in individuals with Parkinson’s disease. The second study was a randomized controlled clinical trial aimed at evaluating and comparing the effects of different physical intervention modalities—aerobic training, resistance training, and task specific training on motor symptoms, manual dexterity, and brain oscillatory activity in individuals with Parkinson’s disease. Thirty-seven participants, with a mean age of 62 years and presenting upper limb functional deficits, completed the study. Participants were randomized into four groups: aerobic training (AT), resistance training (RT), task specific training (TT), and control group (CG). The AT group performed 30 minutes of upper limb cycling using a portable cycle ergometer at an intensity of 50–70% of heart rate reserve. The RT group performed two sets of 8 to 12 repetitions for each exercise, with a two-minute rest between sets, at an intensity of 50–70% of one-repetition maximum (1-RM), determined by the 1-RM test. Free weights and an upper limb exercise machine were used for the resistance exercises. The TT group performed three activities aimed at improving reach, grasp, and manipulation for 30 minutes. All intervention sessions were conducted three times per week for eight weeks. Motor symptoms were assessed using part III of the Unified Parkinson’s Disease Rating Scale (UPDRS-III). Manual dexterity was evaluated using the Nine-Hole Peg Test, and quantitative electroencephalography (qEEG) was used to assess brain activity. Two-way ANOVA and the Scheirer–Ray–Hare test were used to evaluate the effects of time and group on clinical variables, and group and brain region on EEG band power. The level of statistical significance was set at 5%. There was a significant main effect of time (F = 2.80; p = 0.05) and group (F = 2.94; p = 0.03) on the UPDRS-III, with no significant interaction between the factors (F = 1.46; p = 0.23). Tukey's post hoc test showed significant differences in the aerobic (p = 0.04) and resistance training groups (p = 0.04) compared to the control group. No significant group (F = 0.54; p = 0.70) or time effect (F = 0.87; p = 0.35) was observed in the Nine-Hole Peg Test. Additionally, the interventions had a significant effect on the low-alpha sub-band (F = 4.85; p = 0.003) and the alpha band (F = 5.10; p = 0.003), regardless of brain region, in the task specific training group compared to the control group (p = 0.001). For the beta band and low-beta sub-band, there was a main effect of the interventions (F = 5.56; p = 0.001) and (F = 7.59; p < 0.001), with no effect of brain region and no interaction between factors. Tukey's post hoc analysis revealed a significant difference in low-beta in the task specific training group compared to the control group (p < 0.001), and in beta for the resistance training (p = 0.007), aerobic training (p = 0.008), and task specific training (p = 0.004) groups compared to the control group. In conclusion, task specific training based on activities of daily living significantly improved motor symptoms and reduced alpha, low-alpha and low-beta spectral power in individuals with Parkinson’s disease. Furthermore, all interventions caused a significant reduction in beta spectral power, with no difference between them and regardless of brain region. Therefore, the studies presented in this thesis support the importance of physical exercise as a non-pharmacological strategy within the therapeutic plan for this population. In the systematic review, the meta-analysis showed a significant effect of activity-based training on fine manual dexterity compared to other active interventions, while the clinical trial demonstrated a significant improvement in motor symptoms among those who received either aerobic or resistance training. Finally, all proposed interventions resulted in significant changes in brain oscillatory activity.
Effects of physical exercise on manual dexterity, motor symptoms, and brain plasticity in individuals with Parkinson's disease
Keywords: Doenca de Parkinson; Exercício aeróbio; Exercício resistido; Treino específico da tarefa; Destreza manual; Sintomas motores; Oscilação cerebral; Parkinson's disease; Aerobic exercise; Strength training; Task-specific training; Manual dexterity; Motor symptoms; Cerebral oscilation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL